Colour of tropical wood and discolouration due to simulated sunlight - Jana Baar; Vladimír Gryc (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2010)
This study investigated the wood surface discolouration due to simulated sunlight of three tropical woods native in South America. These woods are commonly used in the Czech Republic. Wood of jatoba (Hymenea courbaril L.), massaranduba (Manilkara bidentata A. Chev.) and tigerwood (Astronium graveolens Jacq.) was exposed to treatment by light of xenon-arc lamp, which simulates outdoor sunlight, for 144 hours. Colour measurements of exposed and non-exposed areas of samples were performed by means of spectrophotometer measuring in CIEL*a*b* colour system. The resulting wood discolouration was evaluated according to value of the overall colour change ∆E*. Changes of particular parameters (L*, a* and b*) were also observed during exposure. The wood surface darkened rapidly during the first hours of exposure to simulated sunlight, then samples showed only a slight increase in lightness. After 144 hours of sunlight irradiation the values of chromaticity coordinates were lower compared with the original surface. The initial variations in the lightness of different wood decreased to the minimum after exposure. The most distinctive discolouration of wood was found in the initially brightest wood tigerwood, the darkest massaranduba was affected the least.